2021
DOI: 10.3390/ijerph18041891
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Medical Resource of Patients with Diabetic Foot Ulcer: A Nationwide Population-Based Retrospective Cohort Study for 2001–2015 in Taiwan

Abstract: Diabetic foot ulcer (DFU) is one of the common complications of diabetes. DFU can cause a huge medical and financial burden due to infections, compromise the quality of life, and increase the mortality rate in patients. However, the consumption of medical resources for DFU is rarely mentioned. A retrospective cohort study was performed. Data were obtained from the National Health Insurance Research Database of Taiwan, and the prevalence and medical utilization data for DFU in 2001–2015 were extracted, followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Older patients with diabetic foot should receive more attention because they are always accompanied by other diseases and also, some studies have found that older diabetic patients are at higher risk of developing diabetic foot ulcers and their incidence may be higher ( 19 ). The prevalence of diabetic foot is not low, roughly 6% ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Older patients with diabetic foot should receive more attention because they are always accompanied by other diseases and also, some studies have found that older diabetic patients are at higher risk of developing diabetic foot ulcers and their incidence may be higher ( 19 ). The prevalence of diabetic foot is not low, roughly 6% ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic foot ulcers (DFUs) are a severe and common complication of diabetes mellitus (DM), with a lifetime incidence that ranges from 15 to 25% among individuals with diabetes [1]. As the prevalence of diabetes increases all over the world, the number of patients with a DFU is also growing [2], making it a global public health issue [3]. In fact, DFUs are a leading cause of hospitalization in patients with DM [4], often preceding infection, lower extremity amputation or, ultimately, premature death [5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is a classic example of a chronic disease that continues to be a financial burden to many countries’ healthcare systems. It has been estimated that in Taiwan, a country that has a high prevalence of diabetic mellitus (DM), ~ 15% of DM patients suffer from diabetic wounds (Tai et al 2021 ). On average, these patients can spend 12.7 ± 11.8 days in hospitals (Cheng et al 2019 ), which can incur a huge cost to most patients and their families, both financially and emotionally.…”
Section: Introductionmentioning
confidence: 99%
“…To date, stem cell therapy is the most effective method of treating any diabetic wound, as treatment enhances re-epithelization and angiogenesis, and downregulates profound immune response (Carstens et al 2021 ). However, the cost per treatment is enormous, especially when most of the patients with diabetic wounds are characterized as low income (Tai et al 2021 ). Accordingly, there is a growing need for non-stem cell related therapy that could be used as a cheaper alternative for patients that with less severe diabetic wounds (Li et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%